2014
DOI: 10.1016/j.jpsychires.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Nonmedical stimulant use among young Asian-Americans, Native Hawaiians/Pacific Islanders, and mixed-race individuals aged 12–34 years in the United States

Abstract: There are concerns over nonmedical use of prescription stimulants among youths, but little is known about the extent of use among young Asian-Americans, Native Hawaiians/Pacific Islanders (NHs/PIs), and mixed-race individuals—the fastest growing segments of the U.S. population. We examined prevalences and correlates of nonmedical stimulant use (NMSU) and disorder (StiUD) for these underrecognized groups. Whites were included as a comparison. Data were from young individuals aged 12–34 years in the 2005–2012 Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 55 publications
0
13
0
2
Order By: Relevance
“…This year’s review also found more studies that included bicultural or multiracial Asian-heritage populations compared to past reviews (e.g., L.-T. Wu et al, 2014). This is an encouraging trend, reflecting the fact that from 2000 to 2010, the multiple-race “White and Asian” population increased by a remarkable 87% in the United States (Jones & Bullock, 2012).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This year’s review also found more studies that included bicultural or multiracial Asian-heritage populations compared to past reviews (e.g., L.-T. Wu et al, 2014). This is an encouraging trend, reflecting the fact that from 2000 to 2010, the multiple-race “White and Asian” population increased by a remarkable 87% in the United States (Jones & Bullock, 2012).…”
Section: Discussionmentioning
confidence: 91%
“…The majority of studies used quantitative-correlational designs with analytical methods such as analysis of variance, linear or logistic regression, and structural equation modeling ( n = 15; e.g., Mukherjea et al, 2014). Among the correlational studies, six used longitudinal designs ( n = 6; Bart et al, 2014; Blanco et al, 2014; Boyd, Corbin, & Fromme, 2014; Jimi Huh, Heesung Shin, et al, 2014; Luczak et al, 2014; L.-T. Wu et al, 2014), and the rest used cross-sectional designs. Other studies used quantitative-experimental designs ( n = 1; L.…”
Section: Resultsmentioning
confidence: 99%
“…Little, Fagan, Muranaka, & Herzog, 2014;Tsang et al, 2014;Williams & Nigg, 2014) and drug/nonmedical stimulant use, resistance, and treatment (n = 3; Bart, Lenz, Straka, & Brundage, 2014;Okamoto, Pel, Helm, & Valdez, 2014;L.-T. Wu, Swartz, Brady, Blazer, & Hoyle, 2014). Other articles studied substance use more generally, covering cigarettes, alcohol, marijuana, or "hard" drugs (n = 8; L. Fang & Schinke, 2014;Helm, Okamoto, Kaliades, & Giroux, 2014;Okamoto, Kulis, Helm, Edwards, & Giroux, 2014;Savage & Mezuk, 2014;.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Articles mainly centered on alcohol use (n = 11; Banerjee et al, 2014;Blanco et al, 2014;Jimi Huh, Heesung Shin, et al, 2014;Jimi Huh, Thing, Abramova, Sami, & Unger, 2014;Lo, Cheng, & Howell, 2014;Mukherjea, Wackowski, Lee, & Delnevo, 2014;Pagano, Lee, & Sin, 2014;Pokhrel, Little, Fagan, Kawamoto, & Herzog, 2014;Pokhrel, Little, Fagan, Muranaka, & Herzog, 2014;Tsang et al, 2014;Williams & Nigg, 2014) and drug/nonmedical stimulant use, resistance, and treatment (n = 3; Bart, Lenz, Straka, & Brundage, 2014;Okamoto, Pel, Helm, & Valdez, 2014;L.-T. Wu, Swartz, Brady, Blazer, & Hoyle, 2014). Other articles studied substance use more generally, covering cigarettes, alcohol, marijuana, or "hard" drugs (n = 8; L. Fang & Schinke, 2014;Helm, Okamoto, Kaliades, & Giroux, 2014;Okamoto, Kulis, Helm, Edwards, & Giroux, 2014;Savage & Mezuk, 2014;.…”
Section: Sexual Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation